2014
DOI: 10.1016/j.forsciint.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear forensic analysis of an unknown uranium ore concentrate sample seized in a criminal investigation in Australia

Abstract: Early in 2009, a state policing agency raided a clandestine drug laboratory in a suburb of a major city in Australia. During the search of the laboratory, a small glass jar labelled "Gamma Source" and containing a green powder was discovered. The powder was radioactive. This paper documents the detailed nuclear forensic analysis undertaken to characterise and identify the material and determine its provenance. Isotopic and impurity content, phase composition, microstructure and other characteristics were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…Despite this progress, no single parameter has yet been identified that is able to discern the identity and origin of unknown UOC samples. Increasingly, combined isotopic fingerprinting approaches are used to constrain the provenance and processing history of samples, and multivariate statistical techniques are used to discriminate between different sources of UOCs (Keegan et al 2008(Keegan et al , 2012(Keegan et al , 2014Bayne et al 2009;Robel et al 2009Robel et al , 2011Sirven et al 2009;Varga et al 2010). Likewise, approaches to chronometry have evolved over time, toward an increasing emphasis on obtaining concordant results from multiple parent, daughter, and granddaughter systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this progress, no single parameter has yet been identified that is able to discern the identity and origin of unknown UOC samples. Increasingly, combined isotopic fingerprinting approaches are used to constrain the provenance and processing history of samples, and multivariate statistical techniques are used to discriminate between different sources of UOCs (Keegan et al 2008(Keegan et al , 2012(Keegan et al , 2014Bayne et al 2009;Robel et al 2009Robel et al , 2011Sirven et al 2009;Varga et al 2010). Likewise, approaches to chronometry have evolved over time, toward an increasing emphasis on obtaining concordant results from multiple parent, daughter, and granddaughter systems.…”
Section: Discussionmentioning
confidence: 99%
“…The second sample yielded a model production date of ∼1962, unexpectedly old but plausible (within the nuclear era). A second Australian seizure occurred in New South Wales (Keegan et al 2014), where a small glass jar labeled "Gamma Source" and containing a green powder was obtained. As with the previous seizure, the sample was thoroughly analyzed at both ANSTO and LLNL for stoichiometry, trace elemental composition, U isotopic composition, particle morphology, and radiochronometry.…”
Section: International Seizuresmentioning
confidence: 99%
“…Observed partitioning of REEs in U oxides appears to be strongly dependent on temperature, fluid chemistry and element availability (hypogene REE source), and thus these elements have been used extensively as forensic indicators (e.g. Fayek, ; Frimmel et al., ; Keegan, Wallenius, Mayer, Varga, & Rasmussen, ; Keegan et al., ; Mayer, Wallenius, & Fanghänel, ; Mayer, Wallenius, & Varga, ; Mercadier et al., ). At high temperatures, particularly above 350°C, incorporation mechanisms that discriminate against available cations based upon size are negated due to the dilational nature of the uraninite structure; this results in a relatively flat CN‐REE pattern (Mercadier et al., ).…”
Section: Uraninitementioning
confidence: 99%
“…9 Isotopic content and trace element impurities can be correlated with process history, and in some cases can provide information on the possible geographic origin of a specimen. [10][11][12][13] Data from a broad array of analytical methods are typically needed to completely characterize a forensic specimen, with each measurement providing a different constraint on the possible process history and origin. Techniques applied in the literature include mass spectrometry, nuclear counting, X-ray fluorescence, and powder X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies of illicit nuclear material have required a combination of rapid analyses at several different facilities to rule out possible origins of the material. [10][11] Here, technical developments in sample preparation and instrument operation at the Molecular Environmental Science (MES) STXM Beamline 11.0.2 of the Advanced Light Source (ALS) are described, with a focus on improved utility and throughput for heterogeneous forensic specimens. Initial results are presented, including baseline spectra acquired from common uranium materials, demonstrations of STXM speciation capability on mixtures of known particulates, and preliminary studies of forensic specimens.…”
Section: Introductionmentioning
confidence: 99%